The Non-Image-Forming Effects of Daylight: An Analysis for Design Practice Purposes - Ting Chen; Zhiyuan Zhang (Buildings)
Daylight plays a crucial role in human health, and as research into its effects expands, it is essential for designers to estimate the non-image-forming impacts of various daylighting and lighting strategies. This allows them to create indoor environments that are both pleasant and comfortable. To support this, daylight measurements were taken in five Chinese cities, focusing on spectral power distribution, correlated color temperature, and illuminance. The study calculated the non-image-forming effects of daylight exposure using metrics like melanopic Equivalent Daylight Illuminance and Circadian Light. A key finding was the development of the action factor SAI, which estimates the potential non-image-forming effects of light in built environments. This factor serves as a proxy for understanding how non-image-forming effects relate to correlated color temperatures. Additionally, the research suggests the possibility of creating a time-variational daylighting and lighting strategy with four distinct periods of non-image-forming effects throughout a 24 h day. These insights could be valuable for architects and designers in optimizing indoor lighting systems.